Structural changes in uterine tissues after uterine artery embolization in patients with leiomyoma complicated by uterine bleeding - G P Titova; M M Damirov; L S Kokov; O N Oleynikova; G E Belozerov (IP Berlin A.V., 2018)
Uterine leiomyoma (UL) is often complicated by the development of uterine bleeding. In urgent gynecology for the implementation of endovascular hemostasis, uterine artery embolization (UAE) is used. Performing UAE allows to stop and/or significantly reduce the intensity of bleeding and prepare a patient for surgical intervention. At the same time, the morphological changes that occur in uterine tissues in operated UL patients after performing the UAE are not studied. The aim was to study the peculiarities of pathomorphological changes in uterine tumors and tissues in operated UL patients complicated by uterine bleeding after performing UAE. Material and methods. The results of morphological changes appearing in tumors and tissues of the uterus in 39 operated UL patients, who were used for stopping uterine bleeding, were analyzed. Results. After applying different types of embolizing agents in macroscopic study of the uterus, signs of ischemia of its tissues were revealed, and the most pronounced disorders were detected in the UL nodes. Morphologically it was established that UAE microemboli resulted in vessel occlusion with increasing thrombosis in their distal sections. UAE was not accompanied by occlusal occlusion of the arteries and resulted in small-scale necrosis of the tumor with complete regeneration of the endometrium. Conclusions. The results of the morphological study showed that after the UAE was performed, the myomatous nodes underwent dystrophic, necrobiotic and necrotic changes. Depending on the nature of occlusion of the uterine arteries, various variants of necrosis (scale and completeness of the process) developed in the tumor tissue, which was aseptic in nature.